Inhibition studies of bacterial α-carbonic anhydrases with phenols - Simone Giovannuzzi; Chad S. Hewitt; Alessio Nocentini; Clemente Capasso; Gabriele Costantino; Daniel P. Flaherty; Claudiu T. Supuran (Taylor & Francis Group, 2022)
The α-class carbonic anhydrases (CAs, EC 4.2.1.1) from the bacterial pathogens Neisseria gonorrhoeae (NgCAα) and Vibrio cholerae (VchCAα) were investigated for their inhibition by a panel of phenols and phenolic acids. Mono-, di- and tri-substituted phenols incorporating additional hydroxyl/hydroxymethyl, amino, acetamido, carboxyl, halogeno and carboxyethenyl moieties were included in the study. The best NgCAα inhibitrs were phenol, 3-aminophenol, 4-hydroxy-benzylalcohol, 3-amino-4-chlorophenol and paracetamol, with KI values of 0.6-1.7 µM. The most effective VchCAα inhibitrs were phenol, 3-amino-4-chlorophenol and 4-hydroxy-benzyl-alcohol, with KI values of 0.7-1.2 µM. Small changes in the phenol scaffold led to drastic effects on the bacterial CA inhibitory activity. This class of underinvestigated bacterial CA inhibitors may thus lead to effective compounds for fighting drug resistant bacteria.